2011
DOI: 10.1029/2011ja016806
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between strong range spreadFand ionospheric scintillations observed in Hainan from 2003 to 2007

Abstract: [1] Data from a DPS-4 Digisonde and an ionospheric scintillation monitor, both located at the low-latitude station Hainan (109.1°E, 19.5°N; dip latitude 9°N), were analyzed to study the strong range spread F (SSF) and its correlation with ionospheric scintillations observed in the period of declining solar cycle 23 from 2003 to 2007. The results show that the maximum and minimum of the occurrence of SSF appeared in nearly the same months as those of the GPS L band scintillations. The variations in SSF occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 22 publications
4
80
0
Order By: Relevance
“…As described by Shi et al . [], for SSF conditions, the bottomside depletions reach the topside ionosphere where they are generally classified as plumes [e.g., Kelley , ]. In this situation, field‐aligned F region irregularities at the walls of the depletions produce strong coherent backscatter that appears as SSF on the ionograms [ Sales et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…As described by Shi et al . [], for SSF conditions, the bottomside depletions reach the topside ionosphere where they are generally classified as plumes [e.g., Kelley , ]. In this situation, field‐aligned F region irregularities at the walls of the depletions produce strong coherent backscatter that appears as SSF on the ionograms [ Sales et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…The term “spread F” was coined to give a visual description of the broadened echo traces seen in ionograms. Range spread F (RSF), which is associated with scintillations in radio signals [ Shi et al , 2011] is most prevalent between sunset and local midnight. The initial phase of the RSF development usually begins near the end of the post‐sunset rise (PSSR) of the F layer, which is a consequence of the pre‐reversal enhancement (PRE) of the zonal electric field [e.g., Clemesha and Wright , 1966].…”
Section: Introductionmentioning
confidence: 99%
“…1 were recorded. A spread F, which could be categorized as strong-range spread F (Shi et al 2011;Alfonsi et al 2013), was observed at 01:10 UT ( Fig. 3b) and at 02:40 UT (Fig.…”
Section: Measurements and Data Analysismentioning
confidence: 99%
“…Moreover, equatorial and low-latitude spread F is often associated with plasma bubbles and scintillations of global positioning system (GPS) signals (Chen et al 2006;Shi et al 2011;Alfonsi et al 2013), which may cause inaccuracies in position determination. It is generally accepted that equatorial spread F (ESF) and plasma bubbles result from Rayleigh-Taylor instability triggered during the uplift of the F layer owing to the prereversal enhancement of the eastward (zonal) electric field and development of the steep plasma density gradient as the bottomside ionosphere becomes depleted after sunset (Fejer et al 1999;Stolle et al 2006;Abdu et al 2009a;Kelley 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation